2018
DOI: 10.3390/en11092202
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Tip Clearance in Propeller, Pump and Turbine

Abstract: Propellers, pumps, and turbines are widely applied in marine equipment, water systems, and hydropower stations. With the increasing demand for energy conservation and environmental protection, the high efficiency and the stable operation of pumps and turbine have been drawing great attention in recent decades. However, the tip clearance between the rotating impeller and the stationary shroud can induce leakage flow and interact with the main stream, introducing complex vortex structures. Consequently, the ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(18 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…As an indispensable important energy conversion device, centrifugal pump is extensively applied in various agricultural and industrial fields. For the reduction of equipment investment and energy consumption, modern centrifugal pumps have developed towards the direction of higher flow capacity, rotation speed, head, and efficiency [1][2][3][4][5]. This means that the vibration problem of centrifugal pump tends to become more prominent due to the increased energy density, and it will inevitably bring about unfavorable effects on the operational safety, stability, and life.…”
Section: Introductionmentioning
confidence: 99%
“…As an indispensable important energy conversion device, centrifugal pump is extensively applied in various agricultural and industrial fields. For the reduction of equipment investment and energy consumption, modern centrifugal pumps have developed towards the direction of higher flow capacity, rotation speed, head, and efficiency [1][2][3][4][5]. This means that the vibration problem of centrifugal pump tends to become more prominent due to the increased energy density, and it will inevitably bring about unfavorable effects on the operational safety, stability, and life.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al. 2225 reviewed the tip clearance in propeller, pump, and turbine in the recent two decades in the perspectives from fundamental physics to engineering applications. They concluded that the tip clearance size and the tip shape are crucial parameters for tip leakage vortex (TLV).…”
Section: Introductionmentioning
confidence: 99%
“…Driven by the pressure gradient inside the clearance of the rotor and casing, tip leakage is an unavoidable phenomenon in the field of turbomachinery, which scholars have studied for a long time in both compressible [1][2][3][4] and incompressible [5][6][7][8] fields. As for axial compressors, tip leakage flow plays an even more significant role due to its close relationship with loss and stall characteristics [9,10], which are highly valued in the design or analyzing processes.…”
Section: Introductionmentioning
confidence: 99%